Optimization of Gear Sprocket Surface Hardness through a Combination of Ice Water Quenching and Shot Peening with Pressure Variations - Bambang Hari Priyambodo; Widia Setiawan; Handoko; Martinus Heru Palmiyanto Palmiyanto; Kaleb Priyanto; Yani Kurniawan (Magister Teknik Mesin Universitas Pancasila, 2026)
The gear sprocket is a transmission system component that operates under repeated torsional and frictional loads, making its surface susceptible to wear. To improve wear resistance, a treatment is required to harden the surface layer without significantly altering its dimensions. This study aims to evaluate the effect of combining ice-water quenching and varying shot peening pressures on the surface hardness and microstructural changes of a medium carbon steel gear sprocket. The specimens were austenitized at 850 °C for 15 minutes and rapidly cooled using ice water. Subsequent shot peening was performed for 20 minutes using 0.6 mm diameter steel shots at pressures of 5, 6, 7, and 8 bar. Surface hardness was measured using the Vickers (HV) method, and microstructural observations were conducted with an optical microscope after 2% Nital etching to identify phase transformations. The results show that ice-water quenching increased the surface hardness from 199 HV to 329 HV, representing an increase of approximately 65% over the untreated condition. The combination of quenching and shot peening further enhanced hardness to 404 HV, 454 HV, 487 HV, and 552 HV at 5, 6, 7, and 8 bar, respectively, with the maximum improvement reaching 177% compared to the untreated specimen. Microstructural analysis revealed fine martensitic structures on the quenched surface and a plastically deformed layer produced by shot impacts. Therefore, the combination of ice-water quenching and shot peening effectively enhances surface hardness and refines the microstructure of gear sprockets, indicating its potential application in improving the transmission components wear resistance.